Thermodynamic Analysis of an Endoreversible Bosonic Quantum Otto Refrigerator under Partial Thermalization - Shofiyah Shofiyah; Trengginas Eka Putra Sutantyo; Zulfi Abdullah (Jurusan Fisika FMIPA Universitas Andalas, 2026)
Quantum refrigerators (QRs) are pivotal in exploring thermodynamic behavior at microscopic scales. This study investigates a quantum Otto refrigerator using a bosonic gas confined in a cubic potential, operating under finite-time thermalization. We derive key thermodynamic quantities analytically, including the coefficient of performance (COP), cooling power, entropy, and cooling rate. Additionally, we investigate how partial thermalization during the isochoric heating and cooling stages influences overall system performance. The findings reveal a trade-off between COP and cooling power, emphasizing the importance of thermalization duration. Notably, by extending the cooling time relative to heating, the COP can be significantly improved, offering a practical approach to optimizing QR performance under realistic conditions.